2006
DOI: 10.1097/00054725-200606000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Role of fecal calprotectin as a biomarker of intestinal inflammation in inflammatory bowel disease

Abstract: Calprotectin is an abundant neutrophil protein found in both plasma and stool that is markedly elevated in infectious and inflammatory conditions, including inflammatory bowel disease (IBD). We conducted a systematic review of the published literature regarding fecal calprotectin to evaluate its potential as a noninvasive marker of neutrophilic intestinal inflammation. Reference ranges for fecal calprotectin have been established in healthy adults and children, and elevated concentrations of fecal calprotectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
291
3
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(322 citation statements)
references
References 53 publications
14
291
3
14
Order By: Relevance
“…29,30 Keohane et al 9 have reported that levels of the microinflammation marker fecal calprotectin in IBD patients are significantly higher in the presence of IBS symptoms than in the absence of such symptoms. [31][32][33] This reports provides further background for the relaionship between IBS and inflammation. In this present research, our invesigation of background factors showed that the duration of disease was significantly longer in CD patients with IBS-like symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…29,30 Keohane et al 9 have reported that levels of the microinflammation marker fecal calprotectin in IBD patients are significantly higher in the presence of IBS symptoms than in the absence of such symptoms. [31][32][33] This reports provides further background for the relaionship between IBS and inflammation. In this present research, our invesigation of background factors showed that the duration of disease was significantly longer in CD patients with IBS-like symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have shown that faecal calprotectin and lactoferrin levels are reliable indicators of the gut inflammatory state. [49][50][51][52] However, most studies found no difference in the faecal levels of calprotectin and lactoferrin between IBS patients and healthy controls. 43,44,49,50,[52][53][54][55][56][57][58][59] Only one publication reported that increased levels of faecal calprotectin were correlated with pain severity; however, this result was observed in children displaying both functional abdominal pain and IBS.…”
Section: Key Pointsmentioning
confidence: 99%
“…Other faecal neutrophil-derived proteins (e.g., lysozyme, myeloperoxidase, granulocyte elastase, S100A12) have been investigated in IBD with less success [8]. Calprotectin, lactoferrin and other proteins are produced in significant Brought to you by | University of Ghent Authenticated Download Date | 2/24/16 4:28 PM amounts by inflammatory cells and these biomarkers correlate well with colorectal and intestinal inflammation [12,13]. The faecal excretion of Indium 111-labelled leukocytes is still the golden standard faecal marker of inflammation.…”
Section: Introductionmentioning
confidence: 99%